Addressing the Environmental Health Workforce Shortage: Unpacking Complexities Associated With the Environmental Health Technician Role. - Dunn, Louise; Ross, Kirstin; Lynch, Zena; Dawson, Henry; Dyjack, David T.; Davis, Gayle; Hannelly, Toni; Mitchell, Graeme; Shaw, Lindsay (Journal of Environmental Health)
Environmental health professionals are crucial in protecting communities from harm by preventing and addressing environmental health threats. Becoming an environmental health professional (EHP) typically requires a degree-level qualification or equivalent in most countries. Globally, a chronic shortage of qualified EHPs has led to greater reliance on the employment of environmental health technicians (EHTs) to address environmental health threats, particularly in regulatory settings. Our article uses a SWOT (strengths, weaknesses, opportunities, and threats) analysis to explore the complexities of this growing workplace trend across several countries. Our findings indicate that while the EHT role offers many benefits, it also presents challenges. To effectively tackle these challenges, we propose a strategic framework consisting of five essential components that are needed to assist in managing the complexities associated with this trend: 1) education and training, 2) role clarity, 3) risk-based task allocation, 4) professional development, and 5) organizational support.